ENGLISH 1 FORCED AND UNDER AGE MARRIAGES IN ISLAMIC REPUBLIC OF PAKISTAN : IN THE LIGHT OF RELEVANT LAWS - Hussain , Amar; Arshad, Muhammad; Kashif, Muhammad (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
The numerous problems of Forced and under age Marriages are quite common and insidious practice and used as a tool of gender-based violence against women and men, though “The Child Marriage Restraint Act, 1929, The Sindh Child Marriages Restraint Act, 2013, The Punjab Marriage Restraint (Amendment) Act, 2015” are intact in the county and we have been seeing that Khyber Pukhtun Khwa and also Balochistan governments have been currently drafting their child marriages acts. Forced and under age, wedlock’s come about frequently in the pretext of gender inequality, poverty, and illiteracy. Resultantly physical, social, psychological, and economic consequences of forced and under-age marriages have become severe on girls and boys, who are usually pulled out of primary or secondary education and more likely to cope with emotional, corporal, and sexual violence. Underage wed locks are generally practiced in cost-effected families, and occurrence of child marriage is greater in poorer families and those with lower levels of education and is also high in fragile states hit by natural catastrophe, child marriages do not end with marriage yet it caused gender-based violence and obviously, females remain at the receiving end. Mostly the population of Pakistan comprises minors and without adequate opportunities poses a threat to the society if not deal with properly and correctly. It needs sober attention to makeover this bulge into a dynamic future.